ANALISIS POTENSI PRODUKSI DAN PERSEPSI MASYARAKAT DALAM PENGEMBANGAN BIOGAS PADA SENTRA USAHA TERNAK SAPI PERAH DI KABUPATEN BOGOR - Alla Asmara; Manuntun Parulian Hutagaol; Salundik Salundik (Jurnal Agribisnis Indonesia, 2013)
All this time, the processing dairy manure into biogas energy to be used for cooking and lighting by households around the center of the dairy business have not been done. The purpose of this study was: (1) identify potential resources and public perception in the development of biogas in the dairy business centers, and (2) identify the potential of biogas energy to be derived from cow manure at a dairy business centers. Based on the calculation, the estimated number of biogas that can be produced each day in the dairy business centers amounted to 258.4 m3/day. Meanwhile public perception, farmer and non-farmer, tend to give a positive assessment of the processing of dairy waste into biogas and willing to use biogas as an energy source for cooking.